Effectiveness of multidisciplinary rehabilitation on functional recovery in post-COVID-19 patients: a multicentric study across Ecuadorian healthcare centers - Yepez, Paola; Martinez-Lemus, Juan D.; Mafla-Viscarra, Alejandra; Pérez, Fernando Ortega; Campos, David Sebastián Peña; Arias, Jorge Elías Rodríguez; Caballero, Evelyn Caballero; Tobar, Mirely; Briones-Zamora, Killen H.; Briones-Claudett, Killen H.; Grunauer, Michelle (Frontiers in Medicine, 2026)
BackgroundPost-COVID-19 condition (PCC) poses a major challenge for health systems, particularly in low- and middle-income countries, where evidence on the benefits of multidisciplinary rehabilitation remains limited.ObjectiveTo evaluate changes in functional and perceived health over 12 weeks of multidisciplinary rehabilitation and to determine whether recovery differed between patients with and without PCC.MethodsWe conducted a multicentric, longitudinal cohort study of adults with confirmed COVID-19 enrolled in a multidisciplinary rehabilitation program. PCFS and AVS were evaluated at baseline and at 4-week intervals through Week 12. Patients were classified by PCC status at enrollment. Group comparisons, longitudinal analyses, and logistic regression models (unadjusted and adjusted) were performed to assess changes over time and factors associated with reduced functional improvement. Analyses were conducted using SPSS V.25 and GraphPad Prism V.10.ResultsA total of 477 patients were enrolled; 354 (74.2%) met PCC criteria at baseline (enrollment), and 123 (25.8%) were classified as non-PCC. Follow-up completion for PCFS was 351 patients at Week 4 (73.6%), 330 at Week 8 (69.2%), and 250 at Week 12 (52.4%). At baseline, PCC patients were younger (p = 0.030), had more comorbidities (p < 0.001), and differed in education (p = 0.007), occupation (p = 0.012), and initial provider type (p = 0.004), while sex did not differ (p = 0.299). Over 12 weeks, PCFS decreased by 0.48 points (95% CI –0.65 to −0.31, p < 0.0001) and AVS increased by 0.68 points (95% CI 0.56–0.80, p < 0.0001). In adjusted models, baseline PCC was strongly associated with lower odds of PCFS improvement (aOR 0.27, 95% CI 0.13–0.56, p < 0.001). AVS improvement did not differ by baseline PCC status (p = 0.062).ConclusionMultidisciplinary rehabilitation improved both functional status and perceived health; however, patients with baseline PCC showed less functional recovery. These findings underscore the importance of early identification of PCC status at enrollment and emphasize the need for targeted rehabilitation.